Sertanejo universitário: apontamentos históricos, estruturais, sonoros e temáticos - Bruno Magalhães de Oliveira Rocha (2019)
In the early 2000s a new generation of musicians flourished which gave rise to a new phase of Brazilian country music. The “university Brazilian country music”, as it became known, is currently the most played song in the country and is often defined as having themes associated with night parties and uncompromising love relationships. The objective of this research is to point out sound, thematic and contextual characteristics that constitute this genre. Therefore, historical facts related to its emergence are approached and a problematization regarding the use of the suffix "university" is presented. Through descriptive analysis of phonographic materials, this dissertation seeks to provide elements that facilitate the understanding of its characteristics, such as instrumentation, rhythmic patterns, theme and musical form, aspects neglected or briefly approached by the available literature on the subject. We also seek to reexamine the periodization of the history of Brazilian country music made by other authors and, from this, to propose a new systematic division of this genre. At the end we point out internal modifications of the “university Brazilian country music” that allow it to be divided into three distinct moments and it is concluded that this style dialogues with the previous phases of the genre not only as an innovation, but as a rescue of characteristics that date back to the oldest periods of the genre